Chemistry dimensions 1 [ VCE units 1 and 2 : VCE units 1 and 2 : Teacher's Resource - Jeffery; Ellett; O'Shea (Melbourne, Australia: Pearson Education Australia, 2007)
Software requiremnet Adobe 6 or greater (provide on this CD), Quick time 6.5 or greater (provide on this CD), Internet Explorer 5x or greater (provide on this CD), Flash player 6 or greater (free download), Microsoft Offices suite
To accompany textbook titled "Chemistry dimensions 1 : VCE units 1 & 2 : Teacher's Resource / Faye Jeffery, Brian Ellett and Pat O'Shea"
CSAM
Keywords: Chemistry -- -- Exam